The Impact of Bullying Victimisation on Mental Wellbeing - Georgios Marios Chrysanthou; Chrysovalantis Vasilakis (Institute of Labor Economics (IZA), 2019)
We investigate the impact of nine types of adolescent (verbal, physical, indirect) school/domestic bullying on life satisfaction, and two mental health outcomes (emotional symptoms and hyperactivity/inattention) using the Understanding Society dataset during 2009-13. Bullying significantly increases hyperactive, inattentive and emotional symptoms and reduces life satisfaction. Non-domestic bullying has a stronger adverse impact on all three mental wellbeing outcomes. Domestic sibling victimisation does not affect life satisfaction. Lower levels of family income increase adolescent hyperactive/inattentive symptoms and reduce life satisfaction. Females are more vulnerable to emotional symptoms while males report higher levels of life satisfaction. Initial conditions precondition hyperactive and inattentive symptoms.
Keywords: C25; C35; J12; J13; I31; I10; 330; bullying; mental health; life satisfaction; unobserved heterogeneity